Biochemical and structural alterations in skeletal muscle following ACL injury: a narrative review - Reyes, T.; Willoughby, D. S. (International Journal of Kinesiology & Sports Science, 2020)
Background: Anterior cruciate ligament (ACL) injuries are some of the most common knee injuries that occur in the US, accounting for around 200,000 documented cases per year. Varying levels of severity can determine whether surgery is required or if physical therapy will suffice. One of the most common complications for patients is that there is significant atrophy of the impacted limb. Yet, there has not been definitive proof explaining this mechanism. Objective: The primary goal for this review was to examine some of the biochemical differences that tend to occur within and surrounding an ACL injury and the mechanisms involved in skeletal muscle atrophy and regenerative capabilities. Outcome: Multiple studies have found a connection between time spent inactive from the injury and the percentage of retained muscle after exercising again. Among decreases in muscle mass and muscle volume changes, analyses have also revealed alterations in alpha-2 macroglobulin, myostatin, heat shock protein-72, mechano GF-C24E, synovial fluid, and histochemical alterations in collagen and cartilaginous states which all seem to be primary factors in regulating effectiveness and speed of recovery from ACL injury. Conclusion: the influx of various cytokines as a response to the initial injury in relation to inflammation change the chemical and physical environment of the knee, making recovery significantly more difficult and time-consuming. Timing of injury, surgery, and re-initiation of movement after surgery are very important factors that can minimize overall damage and reduce recovery time.